Savor : 365 devotions - Niequist, Shauna (Zondervan, 2015)
"In this daily devotional, Shauna Niequist becomes a friend across the pages, sharing her heart with yours, keeping you company, and inviting you into the abundant life God offers. And there are recipes, too, because spiritual living happens not just when we read and pray, but also when we gather with family and friends over dinners and breakfasts and late-night snacks. These recipes are Shauna's staples, and each one should be enjoyed around a table with people you love." --Back Cover